Optimising Fiscal Decentralisation: Addressing Financial Management Challenges in Gorontalo Province - Ibrahim, Danial; Aneta, Asna; Wolok, Eduart; Aneta, Yanti (Policy & Governance Review, 2024)
Fiscal decentralisation is the basic capital to reach better governance, regional development, and fiscal autonomy. This paper discusses financial management barriers and opportunities in the Gorontalo Province, a region with low fiscal autonomy, as shown by its index and heavy dependency on central government transfer. This qualitative research, using data from interviews and document studies, found various inefficiencies in the province, such as incongruence between expenditures and revenues, lack of coordination among stakeholders, non-compliance by taxpayers, and delays in financial reporting. Drawing on the theoretical work of Schick (1998) for a framework for public expenditure management and using empirical evidence, this paper proposes an integrated strategy toward a better fiscal management system, diversification of revenue sources, enhancements in planning techniques, introduction of comprehensive accounting mechanisms, and stakeholder participation. This paper contributes to the debate on fiscal decentralisation by giving practical suggestions on how to achieve fiscal autonomy and promote sustainable development in economically less-developed regions.